FIB synthesis of Bi2Se3 1D nanowires demonstrating the co-existence of Shubnikov–de Haas oscillations and linear magnetoresistance. (30th December 2016) - Bhattacharyya, Biplab; Sharma, Alka; Awana, V P S; Senguttuvan, T D; Husale, Sudhir
Abstract: Since the discovery of topological insulators (TIs), there are considerable interests in demonstrating metallic surface states (SS), their shielded robust nature to the backscattering and study their properties at nanoscale dimensions by fabricating nanodevices. Here we address an important scientific issue related to TI whether one can clearly demonstrate the robustness of topological surface states (TSS) to the presence of disorder that does not break any fundamental symmetry. The simple straightforward method of FIB milling was used to synthesize nanowires of Bi2 Se3 which we believe is an interesting route to test robustness of TSS and the obtained results are new compared to many of the earlier papers on quantum transport in TI demonstrating the robustness of metallic SS to gallium (Ga) doping. In the presence of perpendicular magnetic field, we have observed the co-existence of Shubnikov–de Haas oscillations and linear magnetoresistance (LMR), which was systematically investigated for different channel lengths, indicating the Dirac dispersive surface states. The transport properties and estimated physical parameters shown here demonstrate the robustness of SS to the fabrication tools triggering flexibility to explore new exotic quantum phenomena at nanodevice level.